2012
DOI: 10.1590/s0103-21002012000900025
|View full text |Cite
|
Sign up to set email alerts
|

Nurse competencies for health promotion in the mental health context

Abstract: Objective: To identify the competencies of nurses to health promotion in psychiatric and mental health context. Methods: Integrative review of literature performed through search using the keywords: "mental health" and "professional competence", in the databases SciELO, LILACS, CINAHL, PubMed, Scopus and Cochrane, in the period of 2003 to 2011. 215 studies were identified, of these, six followed the inclusion criteria. Results: Based on the National Panel for Psychiatric Mental Health NP Competencies, the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…A formação profissional, tal como foi expressa pelos respondentes e apoiada por estudiosos da área, já não pode ser limitada à sala de aula e à produção descontextualizada de conhecimento. A formação de profissionais de saúde/ enfermagem precisa de se articular com as exigências sociais emergentes no sentido de alargar as competências interativas e associativas, maximizando o conhecimento sobre a realidade concreta dos indivíduos (Aguiar et al, 2012;Backes et al, 2009). Há uma necessidade urgente de mudança na maneira de produzir conhecimento académico (Cornell et al, 2013).…”
Section: Discussionunclassified
“…A formação profissional, tal como foi expressa pelos respondentes e apoiada por estudiosos da área, já não pode ser limitada à sala de aula e à produção descontextualizada de conhecimento. A formação de profissionais de saúde/ enfermagem precisa de se articular com as exigências sociais emergentes no sentido de alargar as competências interativas e associativas, maximizando o conhecimento sobre a realidade concreta dos indivíduos (Aguiar et al, 2012;Backes et al, 2009). Há uma necessidade urgente de mudança na maneira de produzir conhecimento académico (Cornell et al, 2013).…”
Section: Discussionunclassified
“…Results of an integrative review of literature showed that the nursing competencies needed in mental health promotion are monitoring and ensuring the quality of health care practice, management of patient health/illness status, cultural competence, managing and negotiating health care delivery systems, the nurse practitioner-patient relationship (Aguiar, et al, 2012). A study towards 844 psychiatric nurses who were regularly dealing with patients of psychiatric and substance abuse behaviors showed that nurses need competencies of crisis communication and de-escalation techniques (Rutledge, et al, 2013).…”
Section: Career Choices Of Nursing Studentsmentioning
confidence: 99%
“…In creativity, and be empathic (15,19) . With the current high pace of changes in the health systems, it is necessary to provide a safe and cost-effective services, so it is essential to pay attention to clinical competency which is necessary for providing safety patient and it is the main concerns of many health systems and the top priorities of nursing programs.…”
Section: Introductionmentioning
confidence: 99%